Inactivation of aerosolized surrogates of Bacillus anthracis spores by combustion products of aluminum- and magnesium-based reactive materials: Effect of exposure time. Issue 5 (4th May 2018) - Nakpan, Worrawit; Grinshpun, Sergey A.; Yermakov, Michael; Indugula, Reshmi; Reponen, Tiina; Wang, Song; Schoenitz, Mirko; Dreizin, Edward L.
ABSTRACT: Targeting bioweapon facilities may release biothreat agents into the atmosphere. Bacterial spores such as Bacillus anthracis (Ba) escaping from direct exposure to the fireball potentially represent a high health risk. To mitigate it, reactive materials with biocidal properties are being developed. Aluminum-based iodine-containing compositions (e.g., Al·I2 and Al·B·I2 ) have been shown to inactivate aerosolized simulants of Ba effectively, i.e., by factors exceeding 10 4 when the spores are exposed to their combustion products over a short time (∼0.33 s). This follow-up study aimed at establishing an association between the spore inactivation caused by exposure to combustion products of different materials and the exposure time. Powders of Al, Al·I2, Al·B·I2, Mg, Mg·S, and Mg·B·I2 were combusted, and viable aerosolized endospores of B. thuringiensis var kurstaki (a well-established Ba simulant) were exposed to the released products for relatively short time periods: from ∼0.1 to ∼2 s. The tests were performed at two temperatures in the exposure chamber: ∼170°C and ∼260°C; both temperatures are lower than required for quick thermal inactivation of the spores. The higher temperature and exposure times above 0.33 s generated distinctively higher inactivation levels (as high as ∼10 5 ) for iodine-containing materials. We also observed inactivation levels of up to ∼10 3 at very short exposure times, 0.12s, in the presence of condensing MgO. However, the effect of MgO at longer exposure times became negligible. The biocidal effect of sulfur oxides was found to be weak. The study findings are crucial for establishing strategies and developing reaction models that target specific bioagent inactivation levels. Copyright © 2018 American Association for Aerosol Research